Different Wood Anatomical and Growth Responses in European Beech (Fagus sylvatica L.) at Three Forest Sites in Slovenia - Arnič, Domen; Gričar, Jožica; Jevšenak, Jernej; Božič, Gregor; von Arx, Georg; Prislan, Peter (Frontiers in Plant Science, 2021)
European beech (Fagus sylvatica L.) adapts to local growing conditions to enhance its performance. In response to variations in climatic conditions beech trees adjust leaf phenology, cambial phenology and wood formation patterns which result in different tree-ring widths and wood anatomy. Chronologies of tree ring width and vessel features (i.e., mean vessel area, vessel density and relative conductive area) were produced for the1960-2016 period for three sites that differ in climatic regimes and spring leaf phenology (two early-, and one late- flushing populations). These data were used to investigate long-term relationships between climatic conditions and anatomical features of four quarters of tree-rings at annual and intra-annual scales. In addition, we investigated how tree-ring width and vessel features adjust in response to extreme weather events (i.e., summer drought). We found significant differences in tree-ring width, vessel density and relative conductive area among the selected sites. Precipitation and maximum temperature before and during the growing season were the most important climatic factors affecting tree-ring width and vessel characteristics. We confirmed differences in climate-growth relationships between the selected sites, late flushing beech population at Idrija showing the least pronounced response to climate. Mean vessel area was the only vessel trait that showed no relationship with tree-ring width or other vessel features. The relationship between mean vessel area and climatic factors evaluated at the intra-annual scale indicated that vessels areas in the first quarter of tree-ring were mainly influenced by climatic conditions in the previous growing season, while vessel area in the second to fourth quarters of tree ring width was mainly influenced by maximum temperature and precipitation. When comparing wet and dry years, beech from all sites showed a similar response, with reduced tree-ring width and changes in intra-annual variation in vessel area. Our findings suggest that changes in temperature and precipitation regimes as predicted by most climate change scenarios will affect tree-ring increments and wood structure in beech, yet the response between sites or populations may differ.